Morphological description of a new specimen of Herpetoreas burbrinki Guo et al 2014 (Serpentes: Colubridae) - Peng, Lifang; Huang, Song; Burbrink, Frank T.; Zhang, Yong; Guo, Peng; Wu, Hailong (Zootaxa, 2021)
The original description of Burbrink’s Keelback, Herpetoreas burbrinki was based on a sole damaged specimen collected from Zayu County, Xizang Autonomous Region, China in September 2007. On 16 August 2019, we collected a second live adult female specimen from the type locality. The identity of the species is established based on morphological and molecular comparison with the holotype. One mitochondrial gene (Cytb) and three nuclear genes (C-mos, Rag1, NT3) of the new specimen were sequenced. The four sequences all share the same haplotypes with the holotype. We describe the coloration in life, variation with the type and expand the morphological description of this species.